2021
DOI: 10.29173/wclawr52
|View full text |Cite
|
Sign up to set email alerts
|

“But I Wasn’t There!”

Abstract: Using the exoneree summaries in the Innocence Project and the documentation in the Innocence Record, we analyze the content of the alibis of those who have been wrongly convicted and exonerated with the use of DNA. Sixty-five percent of the 377 DNA exonerees had an alibi. Fifty-one percent reported that their alibi corroborators were friends and/or family members, while only about 10% presented physical evidence to support their alibi. Those with an alibi were significantly less likely to falsely confess than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For example, officers surveyed in Dysart and Strange (2012) stated that the suspects they have interviewed about their alibis had family members, romantic partners and friends as alibi corroborators much more frequently than strangers or acquaintances. Similarly, an archival analysis of 377 DNA exoneration cases also confirmed that alibi evidence from friends and family were more common in the sample (51%) than physical alibi evidence (10%) (Heath et al., 2021). People spend a lot of time with their friends and family members; therefore, it is perhaps not surprising that alibi corroborators are often well‐known to defendants and suspects.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…For example, officers surveyed in Dysart and Strange (2012) stated that the suspects they have interviewed about their alibis had family members, romantic partners and friends as alibi corroborators much more frequently than strangers or acquaintances. Similarly, an archival analysis of 377 DNA exoneration cases also confirmed that alibi evidence from friends and family were more common in the sample (51%) than physical alibi evidence (10%) (Heath et al., 2021). People spend a lot of time with their friends and family members; therefore, it is perhaps not surprising that alibi corroborators are often well‐known to defendants and suspects.…”
Section: Introductionmentioning
confidence: 80%
“…As stated in the introduction, this is concerning because some defendants speak the truth when they claim to have been with close family or friends, and both lab and field research suggests that such motivated witnesses are often asked to corroborate alibi claims (e.g. Heath et al., 2021; Nieuwkamp et al., 2017). Although having an alibi corroborator who is not a family member, like a neighbour, is very beneficial in an alibi defence, it is quite uncommon (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations